Simulación de un autómata bibliotecario controlado por inteligencia artificial (2016)
Taking advantage of advances in the theory of intelligent systems and its increasing implementation in a wide variety of work fields, we develop a simulation of a librarian robot controlled by an intelligent system developed under the CommonKADS methodology, specifically to support the processes of book arranging and searching. Evaluating the performance of the robot into the library of the University of San Buenaventura simulated in the graphic engine UNITY, we demonstrate the effectiveness in performing specified tasks. Grupo de Investigación: Modelamiento y Simulación Computacional. -- Línea de Investigación: Ingeniería del Software. -- Área: ingeniería de software. -- Tema: inteligencia artificial.